Beyond the green woods : the life and landscapes of S. B. Easwaran - Mani, Thattunkal Zachariah (Bangalore, 1994)
Nature in her expansive range and incredible variety, over land and water, in sun and shade, in spring, summer or autumn, is the subject of Easwaran's landscapes. Forest streams and silent pools that reflect a shaft of light through lush foliage, rolling meadows framed by verdant woods, vast glades through which flow streams of sparkling diamonds, lonely jungle ways beneath tropical forests under a tender sun, misty marshy lands where the sky meets the earth in the company of soaring birds, the watery expanse of a lake fringed by vibrant verdure, the wanton waterfalls dancing down craggy slopes through dense forest, or the towering hills that catch the glory of the setting sun take the viewer to a world of peace and tranquillity.
Keywords: Environment